A literature review on integrated perinatal care - Charo Rodríguez; Catherine des Rivières-Pigeon (International Journal of Integrated Care, 2007)
Context: The perinatal period is one during which health care services are in high demand. Like other health care sub-sectors, perinatal health care delivery has undergone significant changes in recent years, such as the integrative wave that has swept through the health care industry since the early 1990s. Purpose: The present study aims at reviewing scholarly work on integrated perinatal care to provide support for policy decision-making. Results: Researchers interested in integrated perinatal care have, by assessing the effectiveness of individual clinical practices and intervention programs, mainly addressed issues of continuity of care and clinical and professional integration. Conclusions: Improvements in perinatal health care delivery appear related not to structurally integrated health care delivery systems, but to organizing modalities that aim to support woman-centred care and cooperative clinical practice.